Highlighting the impact of chitosan on the development of gastroretentive drug delivery systems - Souza, Maurício Palmeira Chaves de [UNESP] (2020)
The development of gastroretentive systems have been growing lately due to the high demand for carriers that increase drug bioavailability and therapeutic effectiveness after oral administration. Most of systems reported up to now are based on chitosan (CS) due to its peculiar properties, such as cationic nature, biodegradability, biocompatibility and important mucoadhesiveness, which make CS a promising biopolymer to design effective gastroretentive systems. In light of this, we reported in this review the CS versatility to fabricate different types of nano- and microstructured gastroretentive systems. For a better understanding of the gastric retention mechanisms, we highlighted expandable, density-based, magnetic, mucoadhesive and superporous systems. The biological and chemical properties of CS, anatomophysiological aspects related to gastrointestinal tract (GIT) and some applications of these systems are also described here. Overall, this review may assist researchers to explore new strategies to design safe and efficient gastroretentive systems in order to popularize them in the treatment of diseases and clinical practices.